Ações e instrumentos de políticas públicas para divulgação científica em Minas Gerais - Silvania Alves Ferreira (2021)
Public perception surveys of science and technology in Brazil have shown that the population's interest in scientific and technological matters is growing, but there is still a large number of people who do not have access to this type of information. It is understood that the formulation, implementation and evaluation of public policies for scientific dissemination to the general public is necessary. In this context, the main objective of this research was to investigate how scientific dissemination is carried out in Minas Gerais. To this end, it identified and analyzed the actions and public policy instruments used by the government of the State of Minas Gerais, through the State Secretariat for Economic Development and its related entities, from 1989 to 2020. Exploratory, qualitative approach and which used the analysis of planning and accountability documents issued by the State, as well as complementary documents such as publications in newspapers, magazines and institutional websites. As a result, no specific public policies that institutionalize and legitimize scientific dissemination were found within the State, but the theme is present in more general policies on science and technology and in normative documents that define the competences and purposes of the secretariat in question. However, several actions were found to promote scientific dissemination in Minas Gerais, such as: awards for science disseminators; training; support for scientific dissemination projects; science and technology public perception research; promotion and organization of scientific events; publications in magazines and on social media. The result of this research is expected to have contributed to the analysis of the space occupied by scientific dissemination in the agenda of public policies for science and technology in the state of Minas Gerais.